Merokok dan implikasinya dalam kalangan guru-guru sekolah kebangsaan daerah Kulaijaya - Basiron @ Badron, Bahroini (2014)
Smoking is a common habit that is practiced in today’s society although it is harmful. The main issue of this research is about smoking and its implications among the primary school teachers in Kulaijaya district. There are six objectives in this research; to identify teachers’ knowledge on Islamic prohibition of smoking; to study the level of awareness among the teachers about the health risk of smoking; to understand the level of teachers’ sensitivity about the smoking rules and prohibitions in particular within the school compound; and to evaluate the effectiveness of nosmoking campaign in accordance to Islamic law. This study also endeavors to analyze the significant difference between respondents’ sensitiveness of smoking prohibitions and age factor, gender, level of education and option. It is also to also analyze the relationship between anti-smoking campaign that is in accordance to Islamic law and sensitiveness of smoking prohibitions. This research employed quantitative research methodology by utilizing questionnaire survey instrument that was constructed based on the pre-determined objectives. This survey was distributed in 16 primary schools in Kulaijaya and a random of 310 respondents among the teachers was selected as a sample. The data was the analyzed using SPSS 18 software. Findings from this research shows that teachers’ knowledge on smoking prohibitions is particularly high with 3.82 mean. Meanwhile, the mean of awareness of smoking risk is 4.27 and the mean of effectiveness of no-smoking campaign in accordance to Islamic laws is 4.39. In the meantime, teachers’ sensitiveness of rules and prohibitions of smoking in school compound shows a moderate mean of 3.60. The overall finding of the analysis shows an average mean of 4.02, that is quite high (SP=0.90). The results also shows that there are no significant differences between awareness of smoking prohibitions in Islam and age factor, education level and options. However, there is a significant difference on sensitiveness of smoking prohibitions between different genders. On the other hand, correlation analysis shows that there is strong relationship between no-smoking campaign and smoking prohibitions awareness. The respondents’ acceptance of smoking banned law proves that no-smoking campaign in accordance to Islamic law must be prioritized in order to reduce the number of smokers in the country.